A poética de Frei Nazareno Confaloni - Silva, Maria Abadia (2020)
In this paper we address preferably to the poetic insight/look of Frei Nazareno Confaloni¿s work a cultivated artist and religious man, as well as a missionary from Italy, who came to Goiás in 1950 when he was 33 years-old and deceased here at the age of 60. He left a valuable legacy in the areas he actuated that is, art, religion and education. For that, in the fisrt chapter - on Poetry, we brought the poetry contained in his life and work, highlighting aspects of his outstanding personality through depositions of people of known importance in the art milieu who were connected or close to the artist. For capturing and understanding a little of his huge imaginary poetical universe, his poetry and his voice, we took hold of the theorical concepts of the great poet Octavio Paz. In chapter two, on Imaginary, we moved forward into the phenomenology, through the concepts of Gaston Bachelard and Gilbert Durand so that we could locate ourselves in his historical, mythological and symbolic worlds and with Mircea Eliade, we moved and discovered his sacred universe. In chapter three, on Alchemy, we collected the alchemical elements to assemble and demonstrate the transformations and its reaches of the Imaginary of Frei N. Confaloni's work, his thematic and expressive representations